Genetic evaluation of some first lactation traits in Murrah buffaloes - TEWARI, REETU; KUMAR, D; SINGH, C B; SINGH, HARPAL (The Indian Journal of Animal Sciences, 2021)
A study was conducted for studying the inheritance pattern of some first lactation traits in Murrah buffaloes. Data on 577 Murrah buffaloes maintained at the farms - Firozpur, Ambala, Jallandhar, Jhansi, Lucknow, Bareilly, Agra and Pantnagar spread over 34 years was used. The traits considered were age at first calving (AFC), first calving interval (FCI), first lactation milk yield (FLMY), first lactation period (FLP), weight at first calving (FCI) and first service period (FSP). The heritability estimates (h2±S.E) for AFC, FCI, FLMY, FLP, WFC and FSP traits were found to be 0.40±0.15, 0.14±0.10, 0.31±0.14, 0.23±0.12, 0.36±0.13 and 0.06±0.0, respectively. The genetic and phenotypic correlations revealed that selection for lower age at first calving and higher lactation milk yield can be used as a selection criterion for the genetic improvement in Murrah buffaloes.